Effectiveness of intravenous ferric carboxymaltose in improving hemoglobin level among postpartum women with moderate-to-severe anemia at a secondary care hospital in Faridabad, Haryana - An interventional study - Shashi Kant; Ravneet Kaur; Farhad Ahamed; Archana Singh; Sumit Malhotra; Rakesh Kumar (Wolters Kluwer Medknow Publications, 2020)
Background: Postpartum anemia is associated with postpartum anxiety, depression, poor cognitive interaction, and delayed infant development. Oral iron is the currently recommended therapy but is associated with gastrointestinal complaints and poor compliance. Parenteral iron dextran may cause serious side effects, whereas iron sucrose requires repeated visits. Intravenous ferric carboxymaltose (FCM) is given as an infusion in a single setting, which is logistically convenient both to patients and health system. It can be particularly beneficial for postpartum women who are usually discharged from health facility 48 h after delivery. Objectives: The objectives of this study were to estimate the change in mean hemoglobin (Hb) level 6 weeks after administration of intravenous FCM and to document any adverse events following administration among postpartum women. Methods: A prospective, interventional follow-up study was conducted from August to December 2018. One hundred eligible postpartum women with Hb level of 5-9.9 g/dl were administered a calculated dose of intravenous FCM based on Ganzoni's formula with Hb target of 12 g/dl. Hb and serum ferritin were measured at baseline and at 6 weeks after FCM infusion and compared for mean increase. Results: There was a significant increase in Hb and serum ferritin levels after administration of FCM. The mean (95% confidence interval) increase in the Hb and serum ferritin after 6 weeks was 4.2 (3.9-4.5) g/dl and 137.3 (113.6-161.0) ng/ml, respectively. No major adverse events were reported. Conclusion: Administration of FCM was safe and effective in the treatment of moderate-to-severe anemia among postpartum women.